Analysis of potential immune-related genes involved in the pathogenesis of ischemia-reperfusion injury following liver transplantation - Guo, Jiayu; Han, Shangting; Chen, Qi; Wang, Tianyu; Yu, Bo; Zhou, Jiangqiao; Qiu, Tao (Frontiers in Immunology, 2023)
Hepatic ischemia-reperfusion (I/R) injury is an unavoidable pathological process that occurs after liver transplantation. While the immune response is known to play a critical role in hepatic I/R injury, immune-related genes have been poorly studied. This study used the gene expression omnibus (GEO) database to conduct a search of three available datasets. Relevant core genes were identified and their functions were enrichedusing different modular analysis methods. Immune and inflammatory functions were shown to play an important role in hepatic I/R injury. Nine immune-related hub genes (SOCS3, JUND, CCL4, NFKBIA, CXCL8, ICAM1, IRF1, TNFAIP3, and JUN) were obtained by taking intersections with immune-related genes. Non-coding RNAs and transcription factors that regulate these hub genes were predicted, and verified the inflammatory cell infiltration and damage in mice with hepatic I/R injury. This study provides new insight into the mechanisms of hepatic I/R injury and identifies an important role for the immune response.